Human Microbiome-Targeted Biotechnological Interventions - Aliwi, Esraa Ayad Abdullah; Ghazi, Tuqa Farooq Faisal; Salman, Hiba Naser Kuraiz; Ahmed, Lava kamaran Abdulla; Dharb, Mayada Hamid Ghafil (American Journal of Biology and Natural Sciences, 2025)
The human microbiome is a complex ecosystem whose imbalance dysbiosis has been implicated in various diseases, yet the mechanisms underlying host-microbiome interactions remain insufficiently understood. This study explores biotechnological interventions, including CRISPR-Cas systems and organoid modeling, to target dysbiosis and restore microbial homeostasis. Employing synthetic biology and gut-on-a-chip models, we examined microbial behavior in simulated human gut environments, focusing on their immunomodulatory and metabolic roles. Findings revealed that targeted modulation using engineered probiotics and CRISPR-based tools can suppress pathobionts, enhance beneficial microbes, and restore eubiosis. These results highlight the potential of microbiome engineering as a personalized, non-invasive strategy for preventing and treating metabolic, autoimmune, and neurological disorders. The integration of gene-editing platforms with advanced modeling technologies presents a promising frontier in precision microbiome therapeutics.